Emily Januszewski: capstone - Januszewski, Emily, artist (Colorado State University. Libraries, 2025)
The artist's statement: Emily Januszewski is a graphic designer and illustrator who began her artistic practice at the base of the Rocky Mountains in Boulder, Colorado. Her education abroad and personal passion for global learning has helped her cultivate a design practice inspired by various cultural and artistic philosophies. Emily's focus as a designer is to use a foundation of strict attention-to-detail backed by communicative empathy to help others realize their goals. Emily's strong background in newspaper and magazine layout, as well as digital illustration has familiarised her with working within a pre established design system. This is best seen in page designs, two-page-spread layouts, photo gallery compositions, and newspaper cover work. She is comfortable, even inspired, by working creatively in a box of visual restrictions. Emily is happy working under consistent hard deadlines and working in a fast-paced collaborative environment, such as a newsroom. Within her illustrative work, Emily does not limit herself to a specific drawing style, preferring to first examine the nature of the project prompt and adapting her linework based on what best suits the piece. She is a fan of bold colors, vintage-inspired typefaces, and experimenting with various digital illustration platforms. When combining illustration and type, Emily is adept at meticulously researching accompanying typefaces that will enhance the work's message. When an appropriate pre-existing typeface is not accessible, her next course of action is typically to create one by hand. Emily's work is a manifestation of multiple international education experiences blended with her American identity. Surrounded by ever-shifting cultural practices as an American, and having studied abroad in Japan and the United Kingdom, Emily's work is often related to travel. Adventures on distant shores have contributed to her passion for working in diverse environments and collaborating with individuals from different cultural backgrounds.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design